Googling gold and mining bad news. (December 2016) - Baur, Dirk G.; Dimpfl, Thomas
Abstract: This paper studies investor's attention to gold price movements by analyzing the relationship between gold price changes and internet search queries for gold. We find a positive relationship of gold price volatility and search queries and a strong asymmetric effect of negative gold price changes on search queries indicating a preference to mine (google) bad news rather than good news. The analysis of silver, palladium and platinum demonstrates that the findings for gold are unique. Highlights: Google search queries are used as a measure for retail investor attention. Strong link between gold returns and investor information demand. Results for silver, palladium and platinum are weak emphasizing gold's special role. Strong asymmetric effect of negative gold price changes on search queries. Results indicate a preference to mine bad news rather than good news.